DEVELOPMENT OF EDUCATIONAL GAME APPLICATIONS AS EARLY CHILDREN'S LEARNING MEDIA - Adii, Petronella (STMIK Pringsewu, 2022)
The development of technology information could increase performance and enable various activities could be held with fast, precise, and accurate so that finally will increase productivity. Technology is one style of life moment this. With android, humans can too get entertainment without going to something place, that is, one of them through the games in the application android. Besides that, there are many game features that are not only as entertainment play however already lots of games for honing power thinking and logic that can introduce material for more interesting for accepted and understood especially by children who are still in age early, they are in a period of most rapid growth and development good physique nor mentally. because of that, the author create educational games based on the system Android operation with the hope that the children could direct use the application game. With getting knowledge more a lot and, changing patterns learn not to be too bored and bored. Educational games this is application learning for a child at an age early starting from around ages 3 to 6 years containing Theory learning about introduction animals, letters, numbers, colors, and fruits. With apply results of educational games this, hope could help children in learning and can increase patterns think creative as well as add more knowledge.